PERAN STRATEGIS KETUA ADAT DALAM PELESTARIAN BUDAYA LOKAL: STUDI KASUS TRADISI TINJU ADAT (ETU) SUKU NATAIA DI DESA OLAIA KABUPATEN NAGEKEO - Maria Fatima Coo; Urbanus Ola; Veronika Ina Assan Boro (Journal Education and Government Wiyata, 2026)
Etu traditional boxing is a type of martial art similar to boxing, but with differences from traditional boxing. A young man who participates in etu does not want to win, but rather to demonstrate his mental and spiritual readiness as a strong indigenous man. He learns to control his emotions, manage his anger, and most importantly, uphold brotherhood. The background of this research is the decreasing participation of the younger generation in the traditional boxing tradition (etu) of the Nataia tribe in Olaia Village, Nagekeo Regency, which can threaten the continuity of local culture. Traditional leaders play a crucial role as guardians of values, motivators of participation, and managers of cultural heritage in preserving the etu tradition. This study aims to describe and analyze the important role of traditional leaders in maintaining this tradition. The method used is a qualitative research approach with a case study approach. Data were collected through interviews and documentation, then analyzed descriptively-thematically. The research findings indicate that traditional leaders are active in maintaining the values ​​and meaning of etu, encouraging the participation of the younger generation, and maintaining traditional facilities and locations. This role is crucial for maintaining cultural identity and ensuring the sustainability of traditions amidst changing times.